Revisiting Schein (1965) Study on the Managerial Values and Attitudes of MBA Students - A. Gonul Demirel (International Review of Management and Marketing, 2015)
As schools are organized networks of socializing experiences which prepare individuals to act in society, MBA programs are the socializing media to prepare the future managers. Our study is “a partial replication” of the study done by Schein (1965). The same constructs are used in the questionnaire of the present study. Assuming that what is valued by managers influences how those individuals make business decisions, we aim to find out the managerial values and attitudes of MBA students. We also aim to draw the attention of the faculty members to think about what attitudes, beliefs, and values MBA students are learning and what might the faculty contributions be to the transfer of managerial values. Therefore, the main question of our study is “What are the major managerial values and attitudes of our MBA students?” A second intended contribution of this study is the validation of the scales. The goal of science is empirical generalization, or knowledge development. Systematically conducted replications with extensions facilitate this goal. Keeping this in mind our reconsidering the original constructs of the Schein (1965) study contributes to the validation of at least some of these original constructs.